The decision-making process in Swiss foreign policy at the beginning of the 21st century - Tomczyk, Michał (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
Available scientific studies on modern external relations of Switzerland provide us with extensive interesting information about their current condition and foundations. Most of them also contain in-depth analyses of the outcomes of Swiss foreign policy, but rarely address the specificity of the decision- making process. The latter is currently undergoing major changes due to the growing influence of Europeanisation and internationalisation. In recent years we can observe some shifts in the distribution of power and the rise of new actors, the modification of consultation procedures or a reduction in the level of conflict. This is especially evident in European policy, which still remains a special case. Based on the available scientific studies and analyses of different socio-economic statistics, a few interesting conclusions can be drawn about the conditions and determinants of the decision-making processes. A point of reference here is provided by the Schengen/Dublin agreement, which was negotiated and signed in 2004, as a part of the second package of bilateral agreements. Based on this interesting example, the issue of the modern shape of decision-making process in foreign policy and its development over the last few years can be addressed.

Dostępne badania naukowe dostarczają nam bardzo interesującej wiedzy na temat aktualnego wymiaru relacji Szwajcarii z innymi państwami. Większość z nich koncentruje się jednakże głównie na poziomie praktyki politycznej tj. efektach określonych decyzji politycznych niż szerszych rozważań teoretycznych. Co za tym idzie, relatywnie mało uwagi poświęca się specyfice procesu decyzyjnego, który w ostatnim czasie uległ znacznym modyfikacjom. Źródła tych zmian należałoby doszukiwać się w postępujących procesach integracyjnych w Europie oraz globalizacji. Zmiany, o których mowa, nabrały szczególnej dynamiki w latach 90. ubiegłego wieku. Związane były zarówno z ewolucją środków decyzyjnych, jak i struktury procesów i koncepcji politycznych. Analizując szczegółowo poszczególne etapy szwajcarskiego procesu decyzyjnego jesteśmy w stanie wskazać szereg istotnych zmian, jak chociażby modyfikacja procedur konsultacji, redukcja poziomu konfliktu, przesunięcia w podziale władzy czy pojawienie się nowych aktorów. Punktem odniesienia w niniejszej pracy są porozumienia z Schengen oraz Dublina, zawarte między Szwajcarią a Unią Europejską w 2004 roku. Stanowią one doskonały przykład, obrazujący ewolucję procesu decyzyjnego, jaki miał miejsce w ciągu ostatnich lat.
Proces decyzyjny w szwajcarskiej polityce zagranicznej na początku XXI wieku
Keywords: foreign policy; decision-making process; Swiss-EU relations; Schengen; Dublin; polityka zagraniczna; proces decyzyjny; stosunki Szwajcaria–UE; Schengen; Dublin